“Go for Gold!” or “just for fun”?—competitions at Special Olympics Unified Sports® at the National Games 2022 - Greve, Steffen; Göb, Tjorven Marie; Süßenbach, Jessica (Frontiers in Sports and Active Living, 2025)
Special Olympics Unified Sports® is a sports program in which individuals with and without intellectual disabilities train and compete together on the same team. This study, designed and conducted in accordance with the Grounded Theory Methodology (GTM), investigates how individuals with and without intellectual disabilities co-experience and negotiate competitive dynamics in Unified Sports® basketball and handball. The study examined the success factors and challenges within this context. Based on 41 interviews players (14 athletes and 27 partners) conducted during the 2022 Special Olympics National Games in Berlin, the findings reveal pronounced hierarchical structures along the lines of disability. Partners often adopt a reserved, supportive role, intentionally holding back their own performance in order to place athletes at the center of gameplay. This approach is also evident in interactions with opposing teams, aiming to create a balanced and sporting experience for people with and without disabilities. Such practices challenge conventional notions of athletic success and point to an alternative logic of competition—one that prioritizes joyful social interaction over winning. At the same time, these support strategies carry the risk of fostering paternalistic dynamics that may limit the athletes' autonomy. Grounded in the methodology of Grounded Theory, the study is being extended through additional data collection at national and international competitions. The goal is to develop a differentiated system of categories and to contribute to a deeper understanding of competition in Unified Sports®.